Digital Transparency System Requirements Analysis for Indonesia's Free Nutritious Meal Program: A Blockchain Approach - Hedy Pamungkas; Andhika Andhika (Riviera Publishing, 2025)
While Indonesia's Free Nutritious Meal Program reaches 82.9 million beneficiaries with a budget of Rp71 trillion a year, it is plagued by transparency challenges in coordinating thousands of vendors and schools across the nation. This study proposes a Multi-stakeholder Transparency Requirement Framework, which systematically incorporates blockchain to fill key information loopholes. The study employed a mixed-methods exploratory sequential design, with semi-structured interviews with 10 stakeholders spanning government, vendor, school, and audit representatives, and document analysis of 58 regulatory and evaluation materials from 2020–2024. This streamlines maximized litany of operational constraints: 85% faced retraction and starkings in real time monitoring with information lagged of 3– 4 days, 89% needed manual amalgamation to data desk of 15– 20 hrs each week to take a call and 92% of felonious results of surveilance relied on tank bag I. By applying MoSCoW, it prioritized 26 requirements to where each were mapped 1:1 with 47 smart contract functions across six core contracts. On the distributed ledger side, the blockchain prototype implementation on Polygon zkEVM exhibited technical feasibility, offering transaction costs lower than 0.01, a processing speed varying from 50 to 200 transactions per second, and a gas reduction of 46.5% from baseline consumption levels. Validated by the stakeholders, it transformed the response time of the government from 72–96 hours to less than 5 minutes, the vendor payment delays were reduced from 14–21 days to less than 24 hours, and the audit processing times improved by 60%. It translates the principles of transparency into something actionable in the context of large-scale social programs, which often struggle with similar corruption-related challenges, and within which the diverse initiatives, such as those illustrated, can be replicated in a systematic manner in the developing world. To enhance the broader utility of the framework, future research should examine its applicability across programs and validate it in multiple regions.